Temperature-Dependent Gentamicin Resistance of Francisella tularensis is Mediated by Uptake Modulation - Loughman, Kathleen; Hall, Jesse; Knowlton, Samantha; Sindeldecker, Devin; Gilson, Tricia; Schmitt, Deanna M.; Birch, James W.-M.; Gajtka, Tara; Kobe, Brianna N.; Florjanczyk, Aleksandr; Ingram, Jenna; Bakshi, Chandra S.; et al. (Frontiers in Microbiology, 2016)
Gentamicin (Gm) is an aminoglycoside commonly used to treat bacterial infections such as tularemia – the disease caused by Francisella tularensis. In addition to being pathogenic, F. tularensis is found in environmental niches such as soil where this bacterium likely encounters Gm producers (Micromonospora sp.). Here we show that F. tularensis exhibits increased resistance to Gm at ambient temperature (26°C) compared to mammalian body temperature (37°C). To evaluate whether F. tularensis was less permeable to Gm at 26°C, a fluorescent marker [Texas Red (Tr)] was conjugated with Gm, yielding Tr-Gm. Bacteria incubated at 26°C showed reduced fluorescence compared to those at 37°C when exposed to Tr-Gm suggesting that uptake of Gm was reduced at 26°C. Unconjugated Gm competitively inhibited uptake of Tr-Gm, demonstrating that this fluorescent compound was taken up similarly to unconjugated Gm. Lysates of F. tularensis bacteria incubated with Gm at 37°C inhibited the growth of Escherichia coli significantly more than lysates from bacteria incubated at 26°C, further indicating reduced uptake at this lower temperature. Other facultative pathogens (Listeria monocytogenes and Klebsiella pneumoniae) exhibited increased resistance to Gm at 26°C suggesting that the results generated using F. tularensis may be generalizable to diverse bacteria. Regulation of the uptake of antibiotics provides a mechanism by which facultative pathogens survive alongside antibiotic-producing microbes in nature.